2009
DOI: 10.1108/09653560911003705
|View full text |Cite
|
Sign up to set email alerts
|

Transforming debris management: considering new essentials

Abstract: PurposeThe purpose of this paper is to review what is known about debris management and acknowledge that the effective removal of debris has positive impacts on communities affected by disaster. Four new concerns are introduced that should be considered during the debris management process. These include the recognition of additional debris types as well as the importance of evidence in crime scene investigations.Design/methodology/approachA literature review on debris management is presented in this paper. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…In addition to disaster generated waste, authors have identified other waste streams that can be indirectly generated post-event, including: excessive unwanted donations (Ekici et al, 2009), large amounts of health care wastes (Petersen, 2004), rotten food from power outages (Luther, 2008) and emergency relief food packaging (Solis et al, 1995).…”
Section: Waste Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to disaster generated waste, authors have identified other waste streams that can be indirectly generated post-event, including: excessive unwanted donations (Ekici et al, 2009), large amounts of health care wastes (Petersen, 2004), rotten food from power outages (Luther, 2008) and emergency relief food packaging (Solis et al, 1995).…”
Section: Waste Compositionmentioning
confidence: 99%
“…The US Army Corps of Engineers (Channell et al, 2009) and Ekici et al (2009) give broader reviews, but are still limited to the US context and to technical aspects of debris management. Karunasena (2009) proposes to review disaster waste management in developing countries with an emphasis on the Sri Lankan context.…”
Section: See End Of Documentmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review article by Brown et al [5] presents previous experiences and guidelines on planning, waste composition and treatment, social aspects, and environmental consequences. Other important qualitative studies summarizing several aspects of disaster debris management include Reinhart and McCreanor [20], McEntire [18], and Ekici et al [8]. Despite the abundance of guidelines, there is lack of quantitative guidance on how to carry out the debris removal activities, which we aim to address in this paper.…”
Section: Pre-disastermentioning
confidence: 99%
“…Brown et al (2011a) revealed a number of gaps in existing legislation, organisational structures and funding mechanisms related to disaster waste management. Thus, emerges the importance of designing early stage strategies for disaster waste management with predefined disaster waste management procedures, adequate capacities of local areas, identified recyclable material and disposing sites for sustainable disaster waste management (Baycan and Petersen, 2002;Baycan, 2004;Basnayake et al, 2005; United Nations Development Programme (UNDP), 2006; Ekici et al, 2009;Moe, 2010;Brown et al, 2011a).Further, it has been emphasised that these strategies need to be anchored to strategic-level disaster waste management policies with flexibility for further development to ensure continuity and sustainability (Baycan and Petersen, 2002; Joint UNEP/OCHA Environment Unit (JEU), 2010). In this context, this paper aims to present a theoretical framework for capacity building in post disaster C&D waste management to attain sustainable post disaster C&D waste management for future resilience.…”
mentioning
confidence: 99%